Application of fats and waxes in combination with ethylcellulose as coating materials for controlled release of diltiazem hydrochloride pellets using fluidized bed technique - Warapun Lekrut (Chulalongkorn University, 2013)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 2001